Estimation of the frequency of inherited germline mutations by whole exome sequencing in ethyl nitrosourea-treated and untreated gpt delta mice. (December 2016) - Masumura, Kenichi; Toyoda-Hokaiwado, Naomi; Ukai, Akiko; Gondo, Yoichi; Honma, Masamitsu; Nohmi, Takehiko
Abstract Background Germline mutations are heritable and may cause health disadvantages in the next generation. To investigate trans-generational mutations, we treated malegpt delta mice withN -ethyl-N -nitrosourea (ENU) (85 mg/kg intraperitoneally, weekly on two occasions). The mice were mated with untreated female mice and offspring were obtained. Whole exome sequencing analyses were performed to identifyde novo mutations in the offspring. Results At 20 weeks after the treatment, thegpt mutant frequencies in the sperm of ENU-treated mice were 21-fold higher than those in the untreated control. Liver DNA was extracted from six mice, including the father, mother, and four offspring from each family of the ENU-treated or untreated mice. In total, 12 DNA samples were subjected to whole exome sequencing analyses. We identifiedde novo mutations in the offspring by comparing single nucleotide variations in the parents and offspring. In the ENU-treated group, we detected 148 mutation candidates in four offspring and 123 (82 %) were confirmed as true mutations by Sanger sequencing. In the control group, we detected 12 candidate mutations, of which, three (25 %) were confirmed. The frequency of inherited mutations in the offspring from the ENU-treated family was 184 × 10−8 per base, which was 17-fold higher than that in the control family (11 × 10−8 per base). Thede novo mutation spectrum in the next generation exhibited characteristic ENU-induced somatic mutations, such as base substitutions at A:T bp. Conclusions These results suggest that direct sequencing analyses can be a useful tool for investigating inherited germline mutations and that the germ cells could be a good endpoint for evaluating germline mutations, which are transmitted to offspring as inherited mutations.